ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI(Studi Kasus : Universitas Bina Darma) - Sari, Fatma (Universitas Bina Darma, 2012)
This study employed research model developed by Thompso et al, (1994) to measure the job fit, long-term conseguences and facilitating condition on information technology utilization. Inmodel consist of three variables to be tested and analyzed as follows: job fit variable, long-term conseguences and facilitating condition. All data in this research were collected usong instrument in the form of questionnaire which has been distributed to 50 respondents. Those respondents were taken from five faculties which consist of Bina Darma University lecturer and employed using computer-based information technology to identify, obtain,integrated and interpret tha data in accomplishing their duties. This research is that there are positive and significant influences among job fit variables, long-term conseguences and facilitating condition model toward in UBD information technology utilization, both partially or simultaneously. Keywords: Job Fit Variable, Long-Term Conseguences and Facilitating Condition